Irreducible Posterolateral Fracture Dislocation of the Knee in an Elderly Patient Treated with Rotating Hinge Total Knee Replacement - Bernardi, Gabriele; Manisera, Maria Teresa; Vallone, Alexander; Tudisco, Cosimo (Joints, 2019)
Knee dislocation is one of the few real orthopaedic emergencies. It is a serious but relative uncommon injury, representing less than 0.02% of all orthopaedic injuries. Especially posterolateral knee dislocation is much rarer condition that is often missed or misdiagnosed. The main feature of this very rare condition is to be irreducible by closed reduction due to the interposition of soft tissues inside the enlarged medial joint space, such as the medial capsule and retinaculum, vastusmedialis, and medial meniscus. The pathognomonic sign of a posterolateral knee dislocation is the anteromedial distal thigh transverse “pucker” or “dimple sign.” We report the case of an 87-year-old man who sustained an irreducible posterolateral fracture dislocation of the knee after being hit by car which has been treated with rotating hinge knee replacement with 1-year of follow-up.
Keywords: knee dislocation; posterolateral knee dislocation; irreducible fracture dislocation; rotating hinge knee replacement